'Bold Tendencies': London Contemporary Music Festival, Peckham multi-storey car park, London, 25–28 July, 1–4 August 2013. (3rd January 2014) - Armstrong, Newton
<x content-type="archive" xml:space="preserve">Abstract</x> There is a certain audacity to four young curators adopting the title 'London Contemporary Music Festival' for their first large-scale collective venture. For a festival that deliberately sets out to sidestep the musical establishment, there's an aspect of calculated provocation in the appropriation of a title that would seem to be the preserve of that establishment. The gesture, however, goes some way further than staking a symbolic claim. At the same time as the curators (Aisha Orazbayeva, Sam Mackay, Igor Toronyi-Lalic and Lucy Railton, in collaboration with the commissioning body Bold Tendencies, based at the Peckham Multi-Storey Car Park) have effectively bypassed the establishment networks and funding structures, they have set out a clear alternative narrative about how contemporary music may yet be practised and understood.